Hubungan Ibu Hamil Perokok Pasif dengan Persalinan Preterm di RSUD Dr. Moewardi Surakarta - Imanuddin, Iqbal; Soetrisno, .; Suwandono, Adji (Nexus Kedokteran Klinik, 2014)
Background: Exposure to secondhand smoke among passive smoking pregnant women was known to contain various toxic chemical substances such as Nicotine, Carbon Monoxide, Cadmium, and Polycyclic Aromatic Hydrocarbon. These substances are able to reduce the oxygen supply to the fetus and stimulate the myometrium contraction that could lead to preterm delivery. This study aims to prove the correlation between passive smoking pregnant women and preterm delivery cases. Methods: This study is an analytical observational study using case control approach. This study was conducted in Mawar I ward RSUD Dr. Moewardi, Surakarta. The subjects in this study are 60 who perform delivery in RSUD Dr. Moewardi. Subject preferences were performed using fixed disease-sampling method where subjects are divided into 2 groups, the group consisting of 20 pregnant women with preterm delivery cases and the control group consisting of 40 pregnant women with aterm delivery. Each group was given a questionnaire contains questions regarding passive smokers status as an independent variable, as well as antenatal care (ANC) status, age, and previous preterm delivery history as the confounding factors that will be controlled. Chi square tests and multiple logistic regression analysis were used to analyze the data. Results: The study revealed significant correlation between passive smoking pregnant women and preterm delivery. Pregnant women with secondhand smoke exposure have a preterm delivery risk 9.4 times greater when compared to pregnant woman with no exposure after controlling the confounding factors which is antenatal care and considering the history of previous delivery (p = 0.008; OR = 9.39). Conclusion: There is a significant correlation between passive smoking pregnant women and preterm delivery. Passive smoking pregnant women have a higher risk to experience preterm delivery compared to non-passive smoking pregnant women. Keywords: pregnant women, passive smoking, preterm delivery. Â